Maximizing Business Brand Awareness Through Brand Ambassadors, Content Marketing, and Taglines: An Instagram-Based Study on @npureofficial - Ardhita, Dynda Sovia; Rusdianto, R. Yuniardi (Yayasan Riset dan Pengembangan Intelektual, 2025)
The beauty industry continues to grow rapidly, encouraging brands to create innovative marketing strategies to increase brand awareness amidst increasingly fierce competition. Social media platforms, such as Instagram, are the main means for brands, one of which is N'PURE to attract audience attention by utilizing Brand Ambassadors, Content Marketing, and Taglines. The purpose of this study is to examine the impact of brand ambassadors, content marketing, and taglines on brand awareness on followers of the @npureofficial Instagram account. The method applied in this research is quantitative, with data collected using a questionnaire. A total of 100 respondents were used as samples in this study, with the criteria that followers of the @npureofficial Instagram account were over 17 years old. The data analysis technique used multiple linear regression, Data analysis was carried out using the Statistical Package for the Social Sciences version 30. The findings of this study indicate that brand ambassadors, content marketing and taglines simultaneously and partially have a significant impact on brand awareness. This shows that marketing strategies that include brand ambassadors, content marketing and taglines are effective in increasing brand awareness.